A non-inferiority trial comparing two killed, whole cell, oral cholera vaccines (Cholvax vs. Shanchol) in Dhaka, Bangladesh. Issue 4 (28th January 2022) - Chowdhury, Fahima; Akter, Afroza; Bhuiyan, Taufiqur Rahman; Tauheed, Imam; Teshome, Samuel; Sil, Arijit; Park, Ju Yeon; Chon, Yun; Ferdous, Jannatul; Basher, Salima Raiyan; Ahmed, Faez; Karim, Mahbubul; et al.
Abstract: Bangladesh remains cholera endemic with biannual seasonal peaks causing epidemics. At least 300, 000 severe cases and over 4, 500 deaths occur each year. The available oral cholera vaccines have not yet been adopted for cholera control in Bangladesh due to insufficient number of doses available for endemic control. With a public private partnership, icddr, b initiated a collaboration between vaccine manufacturers in Bangladesh and abroad. A locally manufactured Oral Cholera Vaccine (OCV) named Cholvax became available for testing in Bangladesh. We evaluated the safety and immunogenicity of this locally produced Cholvax (Incepta Vaccine Ltd) inexpensive OCV comparatively to Shanchol (Shantha Biotechnics-Sanofi Pasteur) which is licensed in several countries. We conducted a randomized non-inferiority clinical trial of bivalent, killed oral whole-cell cholera vaccine Cholvax vs. Shanchol in the cholera-endemic area of Mirpur, Dhaka, among three different age cohorts (1–5, 6–17 and 18–45 years) between April 2016 and April 2017. Two vaccine doses were given at 14 days apart to 2, 052 healthy participants. No vaccine-related serious adverse events were reported. There were no significant differences in the frequency of solicited (7.31% vs. 6.73%) and unsolicited (1.46% vs. 1.07%) adverse events reported between the Cholvax and Shanchol groups. Vibriocidal antibody responses among the overall population for O1 Ogawa (81% vs. 77%) and O1 Inaba (83% vs. 84%) serotypes showed that Cholvax was non-inferior to Shanchol, with the non-inferiority margin of −10%. For O1 Inaba, GMT was 462.60 (Test group), 450.84 (Comparator group) with GMR 1.02(95% CI: 0.92, 1.13). For O1 Ogawa, GMT was 419.64 (Test group), 387.22 (Comparator group) with GMR 1.12 (95% CI: 1.02, 1.23). Cholvax was safe and non-inferior to Shanchol in terms of immunogenicity in the different age groups. These results support public use of Cholvax to contribute for reduction of the cholera burden in Bangladesh. ClinicalTrials.gov number: NCT027425581.